General theory of frictional heating with application to rubber friction. (15th April 2015) - Fortunato, G; Ciaravola, V; Furno, A; Lorenz, B; Persson, B N J
Abstract: The energy dissipation in the contact regions between solids in sliding contact can result in high local temperatures which may strongly effect friction and wear. This is the case for rubber sliding on road surfaces at speeds above 1 mm s −1 . We derive equations which describe the frictional heating for solids with arbitrary thermal properties. The theory is applied to rubber friction on road surfaces and we take into account that the frictional energy is partly produced inside the rubber due to the internal friction of rubber and in a thin (nanometer) interfacial layer at the rubber-road contact region. The heat transfer between the rubber and the road surface is described by a heat transfer coefficient which depends on the sliding speed. Numerical results are presented and compared to experimental data. We find that frictional heating results in a kinetic friction force which depends on the orientation of the sliding block, thus violating one of the two basic Leonardo da Vinci 'laws' of friction.